Application of domestic & industrial waste materials in concrete: A review. (2020) - Kishore, Kamal; Gupta, Nakul
Abstract: It is evident that the exploitation of waste increases insignificantly every year worldwide and not recycled as per climatic demand. Therefore, recycling waste consumes energy and produces pollution. In recent years, managing these demolished concrete and waste are the critical problem faced by all world-wide nations. The waste includes demolished concrete, agricultural waste, glass and plastic; causing problem of dispose as once they have been used. In order to deal with such situation, application of such waste as a source in the concrete production can be used by replacing certain parts of original content of aggregates by these aggregates. The recycle of these waste materials in concreting not only assist in managing solid waste but also renders the occurrence of natural resources. Hence this review paper will provide an understanding on adoption of waste materials as a source during the concrete production.